Agents, attachés, and intelligence failures: the Imperial Japanese Navy's efforts to establish espionage networks in the United States before Pearl Harbor. Issue 3 (16th April 2023) - Drabkin, Ron; Kusunoki, K.; Hart, B. W.
ABSTRACT: The 1941 outbreak of war between the United States and Japan was proximately precipitated by the Imperial Japanese Navy at Pearl Harbor. Yet, the IJN was building and cultivating intelligence networks on the U.S. mainland prior. This article presents a comprehensive view of Japanese intelligence efforts against the U.S. based in California and Mexico. A surprising number of relevant sources have only recently come to light. These complement Japanese Foreign Ministry files, oral histories, and Mexican sources to present a more complete story of the IJN's intelligence preparations, successes, and failures before and immediately after Pearl Harbor.